Academic Bullying: Is it a Problem on Your Campus - Cheryl M Smith; Tara R. Underwood (Academic Chairpersons Conference Proceedings, 2015)
Bullies aren't just on the playground or in the halls of local high school. AAUP has identified "bullying" as one of the top ten issues for faculty members and chairs in higher education. Bullying has psychological, physiological, economic and career effects on faculty, staff and administration. Chairpersons, managers and key personnel must respond appropriately and assertively to instances of bullying. Recommendations for identifying bullies and action steps to curtail or prevent bullying will be discussed. An informal survey of conference participants will be conducted about bullying experiences and results will be shared during the presentation.
Keywords: Bullying; prevention; identification; effects; faculty